BKM's Accountability Regarding Mosque Caretaker Wages That Do Not Conform to the Agreement: Imam Syafi'i's Perspective (Case Study of the Muslimin Mandala Mosque) - Erwin; Ahmad Zuhri (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the accountability of the Mosque Prosperity Agency (BKM) of the Muslimin Mandala Mosque regarding the payment of wages to caretakers, which does not comply with the principles of transparency and justice in Islam. The problem arose following a change in mosque management in 2023, resulting in cuts or even complete omissions for no apparent reason. This study aims to analyze the BKM's wages and assess their appropriateness based on the perspective of Imam Shafi'i's jurisprudence.This study uses the field research method to directly explore the practice of managing mosque caretaker wages by the Mosque Prosperity Agency (BKM) at the Muslimin Mandala Mosque.The researcher used a living case study and statute approach. Data were obtained through direct interviews with caretakers, mosque administrators, and community leaders, as well as a review of mosque administrative documents. The findings indicate that there is no clear administrative system for providing wages to caretakers. Wages are given incidentally without any written agreement or certainty of the amount and time, and depend on the voluntary initiative of the administrators and congregation. According to Imam Shafi'i's fiqh (Islamic jurisprudence), this contradicts the principle of ijarah, which states that every work that produces benefits is entitled to fair and clear wages. The hadith of the Prophet Muhammad SAW recommends paying wages before the worker's sweat dries. Therefore, the BKM should develop a written wage system, establish work contracts, schedule regular payments, and implement transparent financial reporting. This study recommends the need to improve the mosque's financial management system to comply with sharia principles, maintain trust, and improve the welfare of caretakers as an important part of the mosque's continued function